Difficulties in Implementing P5 Learning: Causal Factors and Teacher Strategies in Handling Difficulties - Muhammad Rohim Adinugroho; Honest Ummi Kaltsum (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2026)
The implementation of the Pancasila Student Profile Strengthening Project (P5), an essential component of the Independent Curriculum (Curriculum Merdeka) in elementary schools, still faces various challenges, particularly those related to teachers' limited conceptual understanding and lack of school support. This study aims to examine the challenges teachers face in implementing P5, identify contributing factors, and formulate strategies to address them. This study used a descriptive qualitative approach, with elementary school teachers directly involved in implementing P5 as subjects. Data were collected through in-depth interviews supported by observation and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion. The results showed that the main challenges in implementing P5 included low student cooperation and difficulties managing concurrent project assignments. Teachers addressed these obstacles by providing clear instructions, modeling group-work practices, and offering ongoing mentoring and motivation. The study concluded that these strategies were effective in increasing student motivation, engagement, and active participation in P5 activities. The implication of this research is to support Lev Vygotsky's social-constructivist learning theory, which emphasizes the importance of scaffolding, social interaction, and mentoring in developing learning independence.